Genetic basis of maize maternal haploid induction beyond MATRILINEAL and ZmDMP - Trentin, Henrique Uliana; Krause, Matheus Dalsente; Zunjare, Rajkumar Uttamrao; Almeida, Vinícius Costa; Peterlini, Edicarlos; Rotarenco, Valeriy; Frei, Ursula Karoline; Beavis, William Dale; Lübberstedt, Thomas (Frontiers in Plant Science, 2023)
In maize, doubled haploid (DH) lines are created in vivo through crosses with maternal haploid inducers. Their induction ability, usually expressed as haploid induction rate (HIR), is known to be under polygenic control. Although two major genes (MTL and ZmDMP) affecting this trait were recently described, many others remain unknown. To identify them, we designed and performed a SNP based (~9007) genome-wide association study using a large and diverse panel of 159 maternal haploid inducers. Our analyses identified a major gene near MTL, which is present in all inducers and necessary to disrupt haploid induction. We also found a significant quantitative trait loci (QTL) on chromosome 10 using a case-control mapping approach, in which 793 noninducers were used as controls. This QTL harbors a kokopelli ortholog, whose role in maternal haploid induction was recently described in Arabidopsis. QTL with smaller effects were identified on six of the ten maize chromosomes, confirming the polygenic nature of this trait. These QTL could be incorporated into inducer breeding programs through marker-assisted selection approaches. Further improving HIR is important to reduce the cost of DH line production.